2015
DOI: 10.1016/j.geomphys.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Newman–Penrose formalism for Riemannian 3-manifolds

Abstract: Abstract. We adapt the Newman-Penrose formalism in general relativity to the setting of three-dimensional Riemannian geometry, and prove the following results. Given a Riemannian 3-manifold without boundary and a smooth unit vector field k with geodesic flow, if an integral curve of k is hypersurface-orthogonal at a point, then it is so at every point along that curve. Furthermore, if k is complete, hypersurfaceorthogonal, and satisfies Ric(k, k) ≥ 0, then its divergence must be nonnegative. As an application,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In Section 2, we will provide an example of a symplectic form, constructed as in Theorem 1, on the Lorentzian 4-manifold (R × S 3 , −dt 2 ⊕g), whereg is the round metric on the 3-sphere S 3 ; this symplectic form, it turns out, will be the symplectization of a contact form on S 3 whose general form was first discovered in [12]. Specifically, [12] showed that if k is a unit vector field on a Riemannian 3-manifold (M 3 , g) satisfying ∇ k k = 0 and Ric(k, k) > 0, then the 1-form g(k, ·) is a contact form; this was then re-derived, by another means, in [1]. Theorem 1 above is essentially a fourdimensional symplectic version of the construction in [1], made possible for the following reason: because a null vector field k uniquely satisfies k ⊂ k ⊥ , one can thus consider the two-dimensional quotient subbundle k ⊥ /k instead of the full three-dimensional subbundle k ⊥ -this is the crucial (and well known) fact that ultimately makes Theorem 1 possible.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In Section 2, we will provide an example of a symplectic form, constructed as in Theorem 1, on the Lorentzian 4-manifold (R × S 3 , −dt 2 ⊕g), whereg is the round metric on the 3-sphere S 3 ; this symplectic form, it turns out, will be the symplectization of a contact form on S 3 whose general form was first discovered in [12]. Specifically, [12] showed that if k is a unit vector field on a Riemannian 3-manifold (M 3 , g) satisfying ∇ k k = 0 and Ric(k, k) > 0, then the 1-form g(k, ·) is a contact form; this was then re-derived, by another means, in [1]. Theorem 1 above is essentially a fourdimensional symplectic version of the construction in [1], made possible for the following reason: because a null vector field k uniquely satisfies k ⊂ k ⊥ , one can thus consider the two-dimensional quotient subbundle k ⊥ /k instead of the full three-dimensional subbundle k ⊥ -this is the crucial (and well known) fact that ultimately makes Theorem 1 possible.…”
Section: Introductionmentioning
confidence: 96%
“…Together with a function f such that k(f ) is nowhere vanishing, this is enough to ensure that the closed 2-form dg(e f k, ·) is nondegenerate. In Section 2 we also provide two examples to show that: (1) positive Ricci curvature is a sufficient, but by no means necessary, condition to ensure twistedness; (2) the assumption of the completeness of k cannot be dropped from Theorem 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…as in recent work of Aazami [4], where the Newman-Penrose formalism has been applied with interesting effect to methods of symplectic geometry, then the Kähler structure may be recovered from a simple reversal of orientation onM , effectively replacing j by −j. The presence of a Kähler structure on π −1 (M \K) enables the standard presentation of the Bogomolny equation as a time-independent reduction of the anti self-dual property of the connection…”
Section: Introductionmentioning
confidence: 99%
“…as in recent work of Aazami [4], where the Newman-Penrose formalism has been applied with interesting effect to methods of symplectic geometry, then the Kähler structure may be recovered from a simple reversal of orientation on M , effectively replacing j by −j.…”
Section: Introductionmentioning
confidence: 99%